CYCLE DEVELOPMENT PROCESS IMPROVEMENT IN EXTRACTION LEVEL ON PRODUCTION PLAN UNDERGROUND GRASBERG BLOCK CAVE (GBC) AT PT.FREEPORT INDONESIA - Jeffryson Munsaki Rumbewas; Akbar Adhiutama (UNIVERSITAS KEBANGSAAN, 2019)
Abstract:. Development is a process of making aperture (tunnel) is done by dismantling (excavation) both manually and mechanically. The results to be obtained that is in the form of opening holes according to Grasberg Block Cave (GBC Mine) production plan based on the purpose of the open pit function. Propose is done to support other fix facility in order to support the Production Plan in 2018. Completion of a hole openings (Tunnel) with the rule that is a continuous stage (cycle development) that there must be a good control system of development process. Control that is done design engineering and its application in the field. The fact is that in 2015 - 2016, the target gain is not in line with expectations and causes the meter (d Equivalent meter) of operational development at the extraction level in the GBC Underground mine to decrease by 50 - 55% or about 641 meter up to 1000 meter difference of the second plan of the year.Identification of the current problem is the process of progress of opening aperture that has not reached the target because one of the process in the cycle development of Mucking and Hauling not achieved the target because of some basic things. The minimal information and low support of the reporting system caused some strategic decisions to be delayed and caused simultaneous cycles to experience significant constraints. A centralized and fast-accessible Information System from either input or share data by all stakeholders responsible for operational project development tunnel is very supportive. Good motivation greatly affects the performance of each stakeholder working on the project, so that the appropriate approach according to Human needs can be done in order to increase productivity.Project Management with CPM method as well as Human Resource Management (Motivation application of Abraham Maslow) becomes an option in humanizing according to the Root problem obtained by the Current Reality Tree method. The hope is that the development process runs quickly, safely and safely and operational with little operational expense and minimal repetitiveKeywords: cycle development, production plan, underground mine